2019
DOI: 10.1021/acs.jced.8b01185
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibrium of the System {Peanut Biodiesel + Glycerol + Ethanol} at Atmospheric Pressure

Abstract: This study reports experimental data for the liquid–liquid equilibrium (LLE) for a {peanut biodiesel (1) + glycerol (2) + ethanol (3)} system at 303.15 K and 323.15 K at atmospheric pressure. Solubility (binodal) curves were obtained by a cloud-point method. The reliability of the experimental data was confirmed using the Hand and Othmer–Tobias correlations. The regression coefficients were above 0.97 for all data sets. The universal quasichemical model was successfully used to correlate LLE data, which showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…The molar mass used for chicha biodiesel (considered as a pseudocomponent) was obtained from the calculation of the weighted average molar mass of the ethyl esters that make up biodiesel, according to studies reported in the literature. 23,24,32,33 The calculations related to the liquid−liquid equilibrium (with estimated parameters) were obtained from the algorithm of Ferrari et al 34 applying the multiphase liquid−liquid flash algorithm with a phase stability test. The ASOG and NRTL models were used to obtain the activity coefficient.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The molar mass used for chicha biodiesel (considered as a pseudocomponent) was obtained from the calculation of the weighted average molar mass of the ethyl esters that make up biodiesel, according to studies reported in the literature. 23,24,32,33 The calculations related to the liquid−liquid equilibrium (with estimated parameters) were obtained from the algorithm of Ferrari et al 34 applying the multiphase liquid−liquid flash algorithm with a phase stability test. The ASOG and NRTL models were used to obtain the activity coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…All analytic and experimental methods used in this work were reported in recent studies. ,,, However, we will briefly present an overview of experimental techniques.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations